The evidence for lithium in suicide prevention - Roberts, E; Cipriani, A; Geddes, J; Nierenberg, A; Young, A (Royal College of Psychatry, 2018)
We read with interest the recently published meta-analysis of suicide prevention strategies by Riblet et al. However we have some concerns about the authors’ conclusions that “unlike previous reviews, we did not find that lithium significantly reduced suicide.”